(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we aim to investigate the presence of Mycoplasma hominis and Ureaplasma urealyticum antimicrobial susceptibilities at mid-stream urine samples from outpatients who were admitted to Urology, Obstetrics and Gynecology, and Internal Medicine outpatient clinics with dysuria complaints with sterile pyuria negative in first culture results.Material and Method: To test M. Mycoplasma hominis and Ureaplasma urealyticum isolation and antibiotic susceptibility we have used Mycoplasma System Plus (Liofilchem Diagnostics, Italy) kit, which is based on biochemical reaction interpretation.Results: A total of 228 urine samples, from 139 (61%) women and 89 (39%) men with sterile pyuria, were evaluated in the laboratory. Patients were classified according to their ages, 79 (34.6%) of the patients were in 15-35 age group, 60 (26.3%) of the patients were in 36-55 age group, and 89 (39%) were above 56. Seasonal distribution of isolates were also assessed. While Mycoplasma hominis isolation rate in winter months was 13.8% (n:22), in spring it was %8.8 (n:5); Ureaplasma urealyticum isolation rate in winter was 17% (n:27) and %17.5 (n:10) in spring. No isolates could be found in the samples from the summer. The least susceptible antimicrobial to Mycoplasma hominis was ofloxacin while clarithromycin was found relatively less effective on Ureaplasma urealyticum among the tested antimicrobials.Conclusion: In our study, we have considered the urogenital Mycoplasma and Ureaplasma species as pathogens in cases with steril pyuria through implementing a biochemical diagnostic kit in all the laboratories for the isolation, identification, and antimicrobial susceptibility tests.